2019
DOI: 10.1007/s00204-019-02459-w
|View full text |Cite
|
Sign up to set email alerts
|

The Fusarium metabolite culmorin suppresses the in vitro glucuronidation of deoxynivalenol

Abstract: Glucuronidation is a major phase II conjugation pathway in mammals, playing an important role in the detoxification and biotransformation of xenobiotics including mycotoxins such as deoxynivalenol (DON). Culmorin (CUL), a potentially co-occurring Fusarium metabolite, was recently found to inhibit the corresponding detoxification reaction in plants, namely DON-glucoside formation, raising the question whether CUL might affect also the mammalian counterpart. Using cell-free conditions, CUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 69 publications
(107 reference statements)
2
19
0
Order By: Relevance
“…At the moment, the role of sambucinol, a major metabolite of F. culmorum, is unknown. However, there is evidence that culmorin can seriously affect the deoxynivalenol metabolism in mammals by suppressing glucuronidation [47]. Equisetin is a secondary metabolite of F. verticillioides detected in growth media after addition of 100 and 1000 ng mL −1 of FNP (Figure 6a-2).…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, the role of sambucinol, a major metabolite of F. culmorum, is unknown. However, there is evidence that culmorin can seriously affect the deoxynivalenol metabolism in mammals by suppressing glucuronidation [47]. Equisetin is a secondary metabolite of F. verticillioides detected in growth media after addition of 100 and 1000 ng mL −1 of FNP (Figure 6a-2).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, its natural occurrence is always correlated to the occurrence of DON. A recent study showed that CUL is able to inhibit the glucuronidation of DON in human liver microsomes, and thus, its detoxification process [64,65]. These findings make the compound highly relevant regarding synergistic effects, not only for the detoxification of DON, but also for other toxins.…”
Section: Discussionmentioning
confidence: 99%
“…According to one study [51] CULM, 15-hydroxyculmorin, 5-hydroxyculmorin, and 15-hydroxyculmoron were detected after inoculation with F. graminearum, showing enhanced DON toxicity to insects, impacting both growth and mortality, although according to some researchers, CULM and DON can have a synergistic effect on toxicity [52]. Recent findings indicate that CULM can suppress the activity of uridine diphosphate glucosyltransferases (UGTs) that catalyze the glycosylation of DON into the less toxic DON 3-glucoside (D3G) [15]. Compared to DON, in the current research, D3G was found in lower concentrations.…”
Section: Culmorin (Culm) 15-hydroxyculmorin and 5-hydroxyculmorinmentioning
confidence: 99%